2017
DOI: 10.1002/jbm.b.33890
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan conduits filled with simvastatin/Pluronic F‐127 hydrogel promote peripheral nerve regeneration in rats

Abstract: Treating peripheral nerve defects represents a clinical challenge, and nerve conduits lacking an internal scaffold lead to limited large nerve gap regeneration. Here, we bridged 10-mm sciatic nerve defects in rats with a chitosan conduit filled with 0, 0.5, or 1.0 mg of simvastatin in Pluronic F-127 hydrogel. We assessed subsequent nerve regeneration using the sciatic functional index (SFI), electrophysiological assessments, Fluoro-Gold (FG) retrograde tracing, gastrocnemius muscle mass measurements, and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 52 publications
(112 reference statements)
1
27
0
Order By: Relevance
“…For example, Yuan, Zhang, Yang, Wang, and Gu () have shown that chitosan fibers support the adhesion, migration, and proliferation of SCs that result in axonal regeneration in the PNS. Various studies have demonstrated that transplantation of chitosan‐based nerve conduits in 1‐cm gaps or more with or without cells in the rat nerve repair models can induce nerve regeneration and repair damaged nerve (Fregnan et al, ; Guo et al, ; Meyer et al, ; Ruini et al, ; Yin et al, ). A recent study has also reported that chitosan conduits filled with simvastatin/Pluronic F‐127 hydrogel promote peripheral nerve regeneration and motor functional recovery in rats with 10‐mm sciatic nerve defects (Guo et al, ).…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…For example, Yuan, Zhang, Yang, Wang, and Gu () have shown that chitosan fibers support the adhesion, migration, and proliferation of SCs that result in axonal regeneration in the PNS. Various studies have demonstrated that transplantation of chitosan‐based nerve conduits in 1‐cm gaps or more with or without cells in the rat nerve repair models can induce nerve regeneration and repair damaged nerve (Fregnan et al, ; Guo et al, ; Meyer et al, ; Ruini et al, ; Yin et al, ). A recent study has also reported that chitosan conduits filled with simvastatin/Pluronic F‐127 hydrogel promote peripheral nerve regeneration and motor functional recovery in rats with 10‐mm sciatic nerve defects (Guo et al, ).…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…For example, steroids like methylprednisolone were incorporated into chitosan‐based conduits to treat facial nerve injury due to the anti‐edema and anti‐inflammatory effect . Simvastatin is a cholesterol‐lowering drug that can improve neurological disabilities if delivered by chitosan‐based conduits because of their anti‐inflammatory, antioxidant, immunomodulatory, and neuroprotective pleiotropic effects . The last category of drugs is the growth factor.…”
Section: Multiple Applicationsmentioning
confidence: 99%
“…Here, the greatest neural bundle differentiation was observed in simvastatin one-month group (SIM1M) followed by L-carnitine one-month group (LC1M), but this difference was significant only in SIM1M group compared to the others. This can be due to participation of simvastatin in molecular up-regulation (12), and its probable synergistic effect with SCs by stimulating them to secrete NGFs (15). It is known that lipid and cholesterol metabolism is vital for neuron viability during development and also degenerative diseases (18,43).…”
Section: █ Discussionmentioning
confidence: 99%